Experimental studies of nanofluid thermal conductivity enhancement and applications: A review - Tawfik, M. M. (Elsevier, 2016)
In many applications, there is a critical need for enhancing the poor thermal conductivity of conventional fluids in order to develop efficient heat transfer fluids. This requirement can be met through dispersing nanometric particles in a given base fluid such as water, ethylene glycol, oil or air. The resulting nanofluids enhanced thermal conductivity of the base fluids. In order to evaluate this enhancement, nanofluid thermal conductivity is required to be measured. Several methods and techniques are covered in the present contribution. In addition, enhancements recorded experimentally are reviewed and summarized. Different parameters affecting on such enhancement are covered, including: nanoparticle concentration, size, shape and thermal conductivity. In addition, base fluid type, nanofluid bulk temperature and dispersion techniques are also covered parameters. However, nanofluids have the potential to contribute in several practical applications including solar thermal, transportation, electronic cooling, medical, detergency and military applications. In the present work, a brief overview of evolution in the use of nanofluids in some applications has been presented. According to this contribution, there is a critical need for further fundamental and applications of nanofluids studies in order to understand the physical mechanisms of using nanofluids as well as explore different aspects of applications of nanofluids.
Keywords: Nanofluids; Conduction; Measurement; Enhancement; Applications